2005
DOI: 10.1007/s00261-005-0352-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous false aneurysm of the gastroduodenal artery in a hemophilic patient ruptured into the duodenum: case report

Abstract: Pseudoaneurysms of the splanchnic arteries are rare causes of gastrointestinal bleeding. We report a case of a spontaneous gastroduodenal artery false aneurysm ruptured into the duodenum in a patient with hemophilia. The diagnosis was confirmed by spiral computed tomography and magnetic resonance angiography. The patient died from massive gastrointestinal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Nouira et al [15] reported a case of a spontaneous gastroduodenal artery false aneurysm ruptured into the duodenum in a patient with haemophilia. The diagnosis was confirmed by spiral CT and magnetic resonance angiography.…”
Section: Nonmusculoskeletal Pseudoaneurysmsmentioning
confidence: 98%
“…Nouira et al [15] reported a case of a spontaneous gastroduodenal artery false aneurysm ruptured into the duodenum in a patient with haemophilia. The diagnosis was confirmed by spiral CT and magnetic resonance angiography.…”
Section: Nonmusculoskeletal Pseudoaneurysmsmentioning
confidence: 98%
“…They are often asymptomatic, and in 75% of all reported cases, they are diagnosed incidentally. 3 The most serious complication involves rupturing, which occurs in 20% to 80% of all reported cases. 1,2 In fact, gastroduodenal artery aneurysms are considered extremely rare and develop most often after pancreatitis or after pancreatic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the potential risk of rupture, which is given as 20% to 80%, 1,2 asymptomatic nonarteriosclerotic aneurysms should also be treated. 3 Two therapeutic options are available for treatment; endovascular therapy is the preferred therapy for visceral aneurysms, 4…”
Section: Case Reportmentioning
confidence: 99%
“…In a series of seven haemophilic patients with periarticular aneurysms, conservative treatment with FVIII concentrates administration resulted in bleeding with serious clinical consequences [2]. Recently, a fatal case of a ruptured false aneurysm of the gastroduodenal artery in a haemophilic patient was published [3]. These findings lead, in many cases, to the decision to surgically electively treat haemophilic patients with lesions that may result in life‐threatening bleeding, as aneurysm rupture.…”
mentioning
confidence: 99%